2008
DOI: 10.1037/1089-2699.12.3.179
|View full text |Cite
|
Sign up to set email alerts
|

Groupdrink: The effects of alcohol and group process on vigilance errors.

Abstract: This research examined how group processes alter the impact of alcohol on a judgment task requiring vigilance. The authors compared two competing explanations, deindividuation and group monitoring, for the possible effects of alcohol. Two hundred and eighty-six undergraduates with normal drinking habits undertook a vigilance task alone or in four-person groups having consumed either alcohol (calculated to achieve up to .08 blood alcohol content) or a placebo. The vigilance task required them to count occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 43 publications
2
24
1
Order By: Relevance
“…Reynolds, Ortengren, et al, 2006), therefore encompassing both impulsive actions and more thought-out analytical decisions. Furthermore, previous research has found decisions to differ in group contexts dependent of whether these are made with groups (collectively) or in groups (privately but in the presence of others) (Frings, Hopthrow, Abrams, Hulbert, & Gutierrez, 2008). Here, collective group decisions were found to be less erroneous on vigilance tasks, thus supporting the notion that 'two heads are better than one'.…”
Section: Social Influences and Alcohol Effects On Risky Behavioursupporting
confidence: 73%
See 4 more Smart Citations
“…Reynolds, Ortengren, et al, 2006), therefore encompassing both impulsive actions and more thought-out analytical decisions. Furthermore, previous research has found decisions to differ in group contexts dependent of whether these are made with groups (collectively) or in groups (privately but in the presence of others) (Frings, Hopthrow, Abrams, Hulbert, & Gutierrez, 2008). Here, collective group decisions were found to be less erroneous on vigilance tasks, thus supporting the notion that 'two heads are better than one'.…”
Section: Social Influences and Alcohol Effects On Risky Behavioursupporting
confidence: 73%
“…However, previous investigations of intoxication effects have been based on collective group decisions following discussion, rather than on individual decisions in the presence of others (as in the current study). Importantly, decisions made privately in the presence of peers differ from those made collectively as a group both when sober (Centifanti et al, 2016) and intoxicated (Frings et al, 2008). Therefore, these differences may, in part, explain the contrasting findings between the present study and previous work (c.f., Abrams et al, 2006;Hopthrow et al, 2014;).…”
Section: Preliminarycontrasting
confidence: 57%
See 3 more Smart Citations